Efektivitas Video Pembelajaran Youtube dan Simulasi Lapangan dalam Meningkatkan Kesadaran Mitigasi Bencana pada Peserta Didik Sekolah Dasar - Juriyah Juriyah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2019)
Indonesia is highly vulnerable to natural disasters, necessitating disaster mitigation education from an early age. However, disaster awareness among elementary school students remains low due to conventional teaching methods that are theoretical and lack practical experience. This study aims to analyze the effectiveness of YouTube learning videos and field simulations in improving disaster mitigation awareness among elementary school students. The research employed a qualitative descriptive library research method by analyzing national and international accredited journals, textbooks, and scientific publications from 2021 to 2025. Data were collected through literature searches on academic databases using keywords related to YouTube videos, field simulations, and disaster mitigation education. Content analysis was conducted through data reduction, thematic categorization, interpretation, and conclusion drawing. The findings reveal that YouTube learning videos are effective in enhancing cognitive knowledge about disasters through attractive audio-visual content, accessibility, and self-paced learning capabilities. Field simulations are effective in building psychomotor skills and psychological preparedness among students. The integration of both methods in a blended learning model is highly effective in creating optimal synergy following the experiential learning cycle. This study concludes that the integration of YouTube learning videos and field simulations is effective in comprehensively improving disaster mitigation awareness, covering cognitive, affective, and psychomotor domains, and is recommended for implementation in elementary school disaster education curricula.